Typification of the Linnaean name Asperula cynanchica (Rubiaceae) - Ferrer-Gallego, Pedro Pablo (Phytotaxa, 2015)
The typification of Asperula cynanchica L. (Rubiaceae) is discussed. Designation of a lectotype is based on consultation of Linnaeus’s original material and the literature cited in the protologue. The herbarium sheet preseved at UPS [Herb. Burser XIX: 8 (UPS-BURSER)] is designated as lectotype.